KANADI and Class III HD-Zip Gene Families Regulate Embryo Patterning and Modulate Auxin Flow during Embryogenesis in Arabidopsis - Izhaki, Anat (American Society of Plant Biologists, 2007)
Embryo patterning in Arabidopsis thaliana is highly affected when KANADI or Class III HD-Zip genes are compromised. Triple loss-of-function kan1 kan2 kan4 embryos exhibit striking defects in the peripheral–central axis, developing lateral leaf-like organs from the hypocotyls, whereas loss of Class III HD-Zip gene activity results in a loss of bilateral symmetry. Loss of KANADI activity in a Class III HD-Zip mutant background mitigates the defects in bilateral symmetry, implying that the two gene families act antagonistically during embryonic pattern formation. Dynamic patterns of auxin concentration and flux contribute to embryo patterning. Polar cellular distribution of PIN-FORMED1 (PIN1) mediates auxin flow throughout embryogenesis and is required for establishment of the apical–basal axis and bilateral symmetry. Defects in the pattern of PIN1 expression are evident when members of either the KANADI or Class III HD-Zip gene families are compromised. Abnormal expression patterns of PIN1 in KANADI or Class III HD-Zip multiple mutants and the phenotype of plants in which members of both gene families are mutated suggest that pattern formation along the central–peripheral axis results from interplay between auxin and the KANADI and Class III HD-Zip transcription factors, whose defined spatial and temporal expression patterns may also be influenced by auxin.